ANANKASTIK PERSONALITY DISORDER IN SCHIZOPHRENIA PARANOID PATIENT: A CASE REPORT - .., Damarnegara; Andika, A. A. Ngr. (E-Jurnal Medika Udayana; vol 3 no 2 (2014):e-jurnal medika udayana)
Anankastik personality disorder is a health problem that can disturb the activities of person and can accompany a variety of other mental health problems. The patient in this case is a patient with an anankastik or obsessive compulsive personality disorder with the axis I diagnoses is Paranoid Schizophrenia and was given haloperidol 2x5mg, but have not done psychotherapy because the patient has not been cooperative. The prognosis is dependent on patient compliance in taking medication and controls for the setting of the dose, and the support of her family.
Keywords: anankastik personality disorder, paranoid schizophrenia